Analysis on the impact of traffic safety measures on children's gaze behavior and their safety awareness at residential road intersections in Japan. (June 2022) - Tomoda, Mitsuko; Uno, Haruka; Hashimoto, Seiji; Yoshiki, Syuji; Ujihara, Takehito
Highlights: Effects of safety measures on gaze and behavioral consciousness were examined. Experiment was conducted among children who were lower-grade elementary students. Gaze behavior was collected by a non-contact monitor gaze tracking system. Children become more aware to intersections faster by installing footprint mark. Footprint mark also raises children's consciousness to stop at intersections. Abstract: Traffic accidents involving child pedestrians, especially children under 12 years old, frequently occur at residential roads in Japan. The accidents are often caused by children with little walking experience not confirming their surroundings and jumping out on the streets. Therefore, to ensure the safety of child pedestrians, this study examined the effect of six safety measures, involving children's gaze behavior while walking and consciousness of stopping at intersections on residential roads. The gaze measurement experiment and questionnaire survey were conducted on 84 first- to third-grade students. The results showed the usefulness of the footprint mark through the analysis on the child's gaze behavior and consciousness of stopping when walking. The present study clarified that by installing the footprint mark, it is possible to call attention to intersections earlier and increase the feeling of consciousness to stop when they face an intersection. In contrast, color pavement at intersections, which is an effective measure to alert the driver, was not very effective in this study. This suggests that drivers and pedestrians, or adults and children, may have different effects even if the same measures are taken. Thus, traffic safety measures on the roads need to consider the various attributes of road users.